A study of the level of P-10 and some hematological variables in children infected with Entamoeba histolytica. (Journal of the College of Basic Education, 2022)
The study included 24 patients compared to 16 healthy subjects. The results showed a significant increase in the level of white blood cells (10) among the infected (148.75 ± 13.14 pg / ml) compared to healthy subjects (96.68) ± 4.14 pg / ml. 10e6 / ul 3.68 ± 21 0.) compared to healthy subjects (10e6 / ul 4.64 ± 0.17) and a decrease in hemoglobin in the infected (10.54 ± 0.22 g / dl) compared to healthy subjects (11.34 ± 0.19 g / dl) and a decrease in the pressure of red blood cells (PCV) in children The injured (32.44 ± 0.49) compared to the healthy (35.47 ± 0.17). From this we conclude that leukopenia 10 has a major role in the immune response against histolytic amoebiasis, as well as that histolytic amoebiasis affects the level of RBC, Hb, and PCV.